2019
DOI: 10.1186/s13256-019-2158-9
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionately large communicating fourth ventricle: two case reports

Abstract: Background: Management of the disproportionately large communicating fourth ventricle is still problematic. Case presentation: Two cases of disproportionately large communicating fourth ventricle were treated successfully. One was a case of a 51-year-old Han Chinese woman with a complaint of headache and dizziness of 1 year's duration. Magnetic resonance imaging (MRI) demonstrated hydrocephalus with a disproportionately large fourth ventricle. She underwent a ventriculo-peritoneal shunt of the right lateral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…DLCFV is a rare disease characterized by dilatation of the fourth ventricle regardless of lateral ventricle size without definite obstruction of the cerebral aqueduct, indicating patency of the inlet of the fourth ventricle [3]. Its treatment has not been thoroughly established owing to the characteristic hemodynamics of the CSF and a poor understanding of its etiology and pathophysiology [2,4]. Treatment for obstructive hydrocephalus includes ventricular drainage, ventriculoperitoneal shunting Kawabata et al [3] proposed the diagnosis of DLCFV using radiologic imaging of a dilated fourth ventricle and intraoperative endoscopic findings of a patent aqueduct of Sylvius and suggested ETV as a first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DLCFV is a rare disease characterized by dilatation of the fourth ventricle regardless of lateral ventricle size without definite obstruction of the cerebral aqueduct, indicating patency of the inlet of the fourth ventricle [3]. Its treatment has not been thoroughly established owing to the characteristic hemodynamics of the CSF and a poor understanding of its etiology and pathophysiology [2,4]. Treatment for obstructive hydrocephalus includes ventricular drainage, ventriculoperitoneal shunting Kawabata et al [3] proposed the diagnosis of DLCFV using radiologic imaging of a dilated fourth ventricle and intraoperative endoscopic findings of a patent aqueduct of Sylvius and suggested ETV as a first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The search revealed 14 patients who were diagnosed with DLCFV and underwent various successful treatments (Table 2). Lyu et al [2] suggested that DLCFV treatment be individualized. As DLCFV is characterized by a patent aqueduct of Sylvius, it is reasonable to assume that most patients with DLCFV can benefit from supratentorial CSF shunt placement; however, not all are treated because of unresolved infratentorial-supratentorial pressure gradients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation